Use of brillant blue dye on canned cherries - Maldonado, Mariela; Zanonc, Marianela; Polenta, Gustavo Alberto; Denoya, Gabriela Inés; Sanow, Luis Claudio (2017)
Introduction: The toxicity of erythrosine as well as other photochemical and biochemical degradation products thereof has been addressed in several studies. However, it is often employed in the preparation of canned cherries, since its use is allowed by regulatory agencies such as the FDA. Therefore, it would be important to find less risky replacement dyes for their use in food. Methodology: canned cherries were produced by a slow confit process, reaching at least 55° Brix, and were then subjected to commercial pasteurization. Results: Brilliant Blue dyed cherries met the required standard and had a suitable degree of acceptance in the tested population, with the expected parameters being attained in all trials. In addition, the stability test proved that blue dyed cherries remained unchanged, while Erb dyed product suffered an important discoloration. Conclusion: cherries colored by blue brilliant can be elaborated without problem